IDENTIFIKASI KEMAMPUAN BERTANYA CALON GURU BIOLOGI PADA PRAKTEK LAPANGAN PERSEKOLAHAN (PLP) II - D. Mamu, Hartono (Universitas Cokroaminoto Palopo, 2024)
Prospective teachers' ability to ask questions in the learning process needs to be trained to develop their potential in the teaching aspect, through practical activities to introduce the field of learning (PLP) II in schools. This research aims to describe the questioning abilities of prospective biology teacher students in the Biology Education Study Program, Biology Department, FMIPA Universitas Negeri Gorontalo in the PLP II course at Suwawa 1 State High School, Gorontalo Province. The type of research is a survey with a qualitative descriptive approach. The research subjects were 10 (ten) students from the Biology Education Study Program who were programming the PLP II course. The research uses qualitative descriptive methods. Data collection techniques, using observation sheets to observe the questioning ability of each prospective biology teacher; and voice recording devices when prospective teachers ask students questions. Data collection was carried out in 3 (three) learning meetings. The quality of questions refers to the Revised Bloom's Taxonomy. The data analysis technique uses descriptive analysis. The research results show that students' questions in the learning process are dominated by lower level questions or Lower Order Thinking Skill (LOTS) with a percentage value of 88.57%. Meanwhile, for the high level question category or Higher Order Thinking Skill (HOTS), the percentage was 11.43%, lower than LOTS questions.